1994
DOI: 10.1007/bf01058356
|View full text |Cite
|
Sign up to set email alerts
|

Scale for assessing quality of life of children survivors of cranial posterior fossa tumors

Abstract: Our results are comparable to others previously reported, and this supports the validity of our scale. We consider that this scale is applicable to evaluate QL of children survivors of cranial tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…33 Similarly, there are reports demonstrating that diagnosis of a pediatric brain tumor at a younger age appears to be associated with greater disability 21 or decreased strength and overall fitness; 36 whereas others have found that older children were at increased risk of motor impairment. 11,19 However, in each of these cases of contrasting reports, methodological issues for extrapolation to this particular pediatric population were of concern. Two studies used the Bloom Scale, 19,21 1 used no standardized measure, 11 and 1 used a child self-report questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…33 Similarly, there are reports demonstrating that diagnosis of a pediatric brain tumor at a younger age appears to be associated with greater disability 21 or decreased strength and overall fitness; 36 whereas others have found that older children were at increased risk of motor impairment. 11,19 However, in each of these cases of contrasting reports, methodological issues for extrapolation to this particular pediatric population were of concern. Two studies used the Bloom Scale, 19,21 1 used no standardized measure, 11 and 1 used a child self-report questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators related this injury mainly to total brain irradiation dose. Martinez-Climent et al (1994) assessed the HRQL of 39 children who survived posterior fossa tumors, with a median follow-up of 9 years, using a scale developed at their institution. The scale assessed physical and psycho-intellectual functioning and included endocrine and growth status.…”
Section: Response To the Questionnaire Survey And Findings Of The Litmentioning
confidence: 99%
“…A quarter of all children with cancer have a central nervous system (CNS) tumour and these tumours are now the commonest cause of death from cancer in childhood 46. Sixty per cent of children who survive a brain tumour are left with life altering disability 712…”
Section: Introductionmentioning
confidence: 99%